The implementation of standard operational procedure in production process - Vivi Citra Widyawati Napitupulu; Anne Rumondang Malau (Operations Management and Information System Studies, 2022)
Founded in 1916, PT. Siantar Ice Factory is the oldest factory in Pematangsiantar city. This research aims to describe and analyze the application of standard operating procedures (SOP) that occur in the production process at PT. Siantar Ice Factory. Furthermore, this study analyzed the application of the SOP production process to PT. Siantar Ice Factory. The research method used is descriptive-qualitative. Data is collected with interviews, observations, and documentation. Data analysis techniques use data reduction analysis, data presentation, and conclusion withdrawal. The technique used for sampling is purposive sampling. The results showed that PT. Siantar Ice Factory already has SOP in the production process and applies in its production process which includes Standard Operational Procedure (SOP) Machine from the beginning to the end of production takes place; Standard Operational Procedure (SOP) Raw Materials and Raw Material Processing Process, Standard Operational Procedure (SOP) Employee Hygiene in The Production Process.